Electrocatalytic Hydrogenation of Oxygenates using Earth‐Abundant Transition‐Metal Nanoparticles under Mild Conditions. Issue 15 (23rd June 2016) - Carroll, Kyler J.; Burger, Thomas; Langenegger, Lukas; Chavez, Steven; Hunt, Sean T.; Román‐Leshkov, Yuriy; Brushett, Fikile R.
Abstract: Electrocatalytic hydrogenation (ECH) is a sustainable pathway for the synthesis of value‐added organic compounds, provided affordable catalysts with high activity, selectivity and durability are developed. Here, we synthesize Cu/C, Ni/C, and CuNi/C nanoparticles and compare their performance to Pt/C, Ru/C, PtRu/C for the ECH of hydroxyacetone, a bio‐derived feedstock surrogate containing a carbonyl and a hydroxyl functional group. The non‐precious metal electrocatalysts show promising conversion‐time behavior, product selectivities, and Faradaic efficiencies. Ni/C forms propylene glycol with a selectivity of 89 % (at 80 % conversion), while Cu/C catalyzes ECH (52 % selectivity) and hydrodeoxygenation (HDO, 48 % selectivity, accounting for evaporation). CuNi/C shows increased turnover frequencies but reduced ECH selectivity (80 % at 80 % conversion) as compared to the Ni/C catalyst. Importantly, stability studies show that the non‐precious metal catalysts do not leach at operating conditions. Abstract : MITarbeiters of the Month : Electrocatalytic hydrogenation (ECH) is a sustainable pathway for the synthesis of value‐added organic compounds, provided affordable catalysts with high activity, selectivity, and durability are developed. The performance of a series of copper, nickel, and copper–nickel nanoparticles on a carbon support towards ECH of hydroxyacetone is compared to that of ruthenium, platinum, and platinum–ruthenium nanoparticles. The non‐precious metal electrocatalysts show promising conversion–time behavior, product selectivities, and Faradaic efficiencies.